Some Results on Generalized Appell Functions - Castillo P., Jaime; Galué, Leda (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
Recently A.Â  H. Al-Shammery and S.Â  L.Â  Kalla presented generalizations for the Appell”™s functionsÂ Â Â Â  Fi (w, z)Â (i = 1, 2, 3),Â introducingÂ parametersÂ  t, t'. In this paper the generalized Appell”™s functions Fi t, t' (w,z),Â  (i = 1,2,3) are represented in terms of a generalization of the Gauss hypergeometric series 2R1t(Z), in order to establish some integral representations, recurrence relations and differentiation formulas for generalized Appell”™s functions. An application and various particular cases are also presented